f((m+1)²)=-2(m-1)²
f est de la forme f(x) = ax car fonction linéaire
f(x) = -1/2 (x)
on remplace x par ( m+1)²
on développe en se servant des identités remarquables
(a+b)² et (a-b)²
f( m+1)² = -1/2 ( m+1)² = -1/2 ( m² +2m +1)
-2(m-1)² = -2( m² -2m +1)
-1/2 ( m² +2m +1) = -2( m² -2m +1)
-( m² +2m +1) = -4( m² -2m +1)
m² +2m +1 = 4 m² -8m +4
m² +2m +1 -4 m² +8m -4 = 0
-3 m² + 10m - 3 = 0
delta = 10² - 4 * 9 = 64 = 8²
m1= (-b - Vdelta) 2a = (-10 - 8) /( 2*- 3) = 3
m2 = (-b +Vdelta) 2a = (-10 +8) /( 2*- 3) = 1/ 3
m1 = 3
m2 = 1/3
S={ 1/3 ; 3}